Effect of Work Environment and Communication on Employee Satisfaction in PT. Razza Prima Trafo Medan - Rahmad Bahagia; Nur Fadillah Afni (AIBPM Publisher, 2021)
The research objective is to determine the effect of work environment and communication on job satisfaction of employees of PT. Razza Prima Transformer Medan. This study uses multiple linear regression analysis, determination test, t test, and f test with the help of SPSS version 25.00 test. The results of the study answered the problem formulation that there was an influence of the work environment (X1) and communication (X2) on employee job satisfaction (Y) at PT. Razza Prima Transformer Medan, where improving the work environment and communication will increase employee job satisfaction at PT. Razza Prima Transformer Medan. From the results of the study simultaneously the work environment and communication variables have a significant and significant effect on the variable job satisfaction of employees of PT. Razza Prima Transformer Medan is 69.3% while 30.7% is the contribution of other variables that are not included in this regression model.